POTRET SOSIAL EKONOMI BUDAYA MASYARAKAT SEKITAR HUTAN (KASUS PULAU BANDA BESAR) KECAMATAN BANDA NEIRA KABUPATEN MALUKU TENGAH - Latar, Choirul Fachril; Kastanya, Agustinus; Iskar, Iskar (MAKILA, 2023)
This study aims to determine the socio-economic, cultural conditions, and income levels of communities around the forest on Banda Besar Island. The research results show that the community's economic condition depends on forest products managed through gardening (Agroforestry). Data collected through observations and interviews was then analyzed descriptively, qualitatively, and quantitatively. The research results show that the community's economic condition depends on forest products managed through Agroforestry. The social culture of the people on Banda Besar Island is very open to the outside world; the people do not differentiate between immigrants and natives, and ethnic mixing occurs very quickly. Some cultural traditions of communities around the forest include washing wells, buka puang, kombak, papaito, belang, cakalele, and the nutmeg-picking dance. The income of communities around the forest from managing forests using an agroforestry system can increase community income from three types of commodities, namely nutmeg, cloves, and walnuts, obtaining a total average income for communities around the forest of Rp. 16,082,667,-KK/Year and an average.